2022
DOI: 10.1016/j.chest.2021.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Early Referral of Patients With Interstitial Lung Abnormalities

Abstract: on behalf of the ILA Study Group * BACKGROUND: Interstitial lung abnormalities (ILA) may represent undiagnosed early-stage or subclinical interstitial lung disease (ILD). ILAs are often observed incidentally in patients who subsequently develop clinically overt ILD. There is limited information on consensus definitions for, and the appropriate evaluation of, ILA. Early recognition of patients with ILD remains challenging, yet critically important. Expert consensus could inform early recognition and referral.RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 45 publications
(78 reference statements)
0
21
0
1
Order By: Relevance
“…We found that PBMC adrenomedullin levels in DM patients with ILD associated with pulmonary function test results, higher adrenomedullin mRNA levels correlated with worse lung function in DM patients with ILD, which may help assess the severity of ILD ( 33 , 34 ). In addition, deterioration of lung function, especially forced vital capacity (FVC) and DLco, is known to indicate disease progression and to be corelated with prognosis in DM patients with ILD ( 34 ). Therefore, PBMC adrenomedullin levels can be indicative of disease severity and prognosis in these patients.…”
Section: Discussionmentioning
confidence: 81%
“…We found that PBMC adrenomedullin levels in DM patients with ILD associated with pulmonary function test results, higher adrenomedullin mRNA levels correlated with worse lung function in DM patients with ILD, which may help assess the severity of ILD ( 33 , 34 ). In addition, deterioration of lung function, especially forced vital capacity (FVC) and DLco, is known to indicate disease progression and to be corelated with prognosis in DM patients with ILD ( 34 ). Therefore, PBMC adrenomedullin levels can be indicative of disease severity and prognosis in these patients.…”
Section: Discussionmentioning
confidence: 81%
“…These metrics help to quantify the severity of ILD. Therefore, resistin mRNA levels are indicative of DM-ILD severity and disease activity ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Right heart catheterization was undertaken only on patients with severe symptoms or abnormal echocardiographic signs that required confirmation. ILD was considered present according to a published algorithm based on radiographic abnormalities compatible with ILD on high‐resolution computed tomography or, if high‐resolution computed tomography was not available, by chest radiograph 24,25 . The presence of scleroderma renal crisis was obtained by chart review and patient history.…”
Section: Methodsmentioning
confidence: 99%